Prophylactic arrhythmia surgery in association with congenital heart disease - Mavroudis, Constantine (Transl Pediatr, 2016)
Certain congenital heart anomalies make patients more susceptible to arrhythmia development throughout their lives. This poses the question whether prophylactic arrhythmia surgery should be incorporated into reparative open heart procedures for congenital heart disease. There is currently no consensus on what constitutes a standard prophylactic procedure, owing to the questions that remain regarding lesions to be performed; energy sources to use; proximity of energy source or incisions to coronary arteries, sinoatrial node, atrioventricular node; circumstances for right atrial, left atrial, or biatrial appendectomy; and whether to perform a right, left, or biatrial maze procedure. These considerations are important because prophylactic arrhythmia procedures are performed without knowing if the patient will actually develop an arrhythmia in his or her lifetime. By reviewing and summarizing the literature, congenital heart disease patients who are at risk for developing atrial arrhythmias can be identified and lesion sets can be suggested in an effort to standardize experimental protocols for prophylactic arrhythmia surgery.